Succinic acid inhibits the activity of cytochrome P450 (CYP450) enzymes - Hao Wang; Bingyan Xia; Mei Lin; Yongpeng Wang; Bin Sun; Yuzhu Li (Taylor & Francis Group, 2020)
Context Succinic acid, extracted from amber, is widely used in cardiovascular therapy. Objective The effect of succinic acid on the activity of cytochrome P450 (CYP450) enzymes was investigated in this study. Materials and methods The effect of succinic acid (100 μM) on the activity of eight isoforms of CYP450 (i.e., 1A2, 3A4, 2A6, 2E1, 2D6, 2C9, 2C19 and 2C8) was investigated compared to the specific inhibitor and blank controls in pooled human liver microsomes in vitro. The inhibition of CYPs was fitted with competitive or non-competitive inhibition models and corresponding parameters were also obtained. Results Succinic acid exerted inhibitory effect on the activity of CYP3A4, 2D6, and 2C9 with the IC50 values of 12.82, 14.53, and 19.60 μM, respectively. Succinic acid inhibited the activity of CYP3A4 in a non-competitive manner with the Ki value of 6.18 μM, and inhibited CYP2D6 and 2C9 competitively with Ki values of 7.40 and 9.48 μM, respectively. Furthermore, the inhibition of CYP3A4 was found to be time-dependent with the KI/Kinact value of 6.52/0.051 min−1·μM−1. Discussion and conclusions Succinic acid showed in vitro inhibitory effects on the activity of CYP3A4, 2D6, and 2C9, which indicated the potential drug-drug interactions. Succinic acid should be carefully co-administrated with the drugs metabolized by CYP3A4, 2D6, and 2C9.